Endemic Goiter in Kitâbu Divanü Lügat-it Türk: Evidence From 11th Century - Yusuf Kemal Kemaloğlu (Gazi Medical Journal)
To present the information about endemic goiter noted in Kitâbu Divanü Lügat-it Türk (KDLT), which was overlooked in the history of medicine. The information about endemic goiter noted in the English and Turkish copies of the KDLT was reviewed in relation to goiter and thyroid hyperplasia. Further, KDLT and his author were briefly searched for using historical sources. In KDLT, which was prepared for introduction of Turkish and Turks to the Arabians in the 11th century, Mahmûd El Kashgari (1008-1102), a lexicographer of Turkic languages, noted that the “boquq” (goiter) was widespread among the Turks living in Fargana and Siqni in the Central Asia during generations. By this report, a rare source, and the first direct evidence of endemic goiter in Turks living in central Asia, has been added to the historical corpus of endemic goiter. The information related to endemic goiter in KDLT was previously not known in the medical literature, but it was in accordance with the notes of Avicenna and observations of Marco Polo, who both reported goiter in Asia in the 11th to 13th centuries.